A Note on the Use of Uranine Tracer to Visualize Radionuclide Migration Experiments: Some Observations and Problems. (3rd July 2019) - Winberg-Wang, Helen; Neretnieks, Ivars; Voutilainen, Mikko
Abstract: Uranine is a dye commonly used in tracer experiments; it is chosen for its high visibility even at low concentrations. Uranine solutions are slightly denser than water at the same temperature. However, in laboratory experiments uranine solutions have been known to occasionally show unpredictable flow behaviors. This paper investigates the possible effect of light-induced density change to explain some of these behaviors. Uranine has a wide light absorption spectrum for visible light, which can heat the dye solution and lower its density to below that of the surrounding water, which induces buoyancy-driven flow. Simulations are made in both one dimension and two dimensions to determine the extent of the effect. The results are then compared to different experiments with unanticipated flow patterns.